Performance Improvement of Tetraethylorthosilicate Consolidated Andesite Rock by Adding Titanium Tetraisopropoxyde and Silica Particles - Nahar Cahyandaru; Endang Tri Wahyuni; Nuryono Nuryono (Indonesian Journal of Chemistry, 2021)
A study to improve the performance of andesite mortar and rock consolidated with tetraethylorthosilicate (TEOS) sol and a solvent of ethanol in the presence of titanium tetraisopropoxyde (TTIP) and silica particles has been conducted. The improvements include minimizing the shrinkage using silica particles from rice husk ash, rheological property suitability of the consolidant, and mechanical properties of the consolidated mortar and rock. The effect of TTIP concentration, ethanol volume, and addition of the silica particles on rheological properties of TEOS-based consolidant, and also mechanical properties of the consolidated mortar and rock were evaluated. The results showed that the increase of TTIP content in the consolidant shortens the gelling time, and the weight percentage ratio of TTIP:TEOS:ethanol of 5%:55%:40% was the optimum composition for the consolidation. Consolidation of andesite block using that composition significantly increased the compressive strength up to 57.61% (0.58 kgf/mm2). The addition of 2% of silica particles into the consolidant decreased the gel shrinkage and increased the Young modulus of the mortar. The presence of water in the andesite matrix reduced the consolidation performance, and 0.5% was the maximum percentage of water content acceptable for the consolidation.